A dual infection of two microscopic fungi on common milkweed (Asclepias syriaca) in Hajdúság region (East-Hungary) - Tóth, Tamás (Acta Agraria Debreceniensis, 2017)
Common milkweed (Asclepias syriaca L.) is one of the most noxious and invasive weed species in Hungary. A. syriaca invades arable lands, horticultural and forestry plantations, natural and semi-natural habitats too. In cases of field crops it can cause considerable yield losses mostly in maize (2–10%), soybean (12–32%) and sorghum (4–29%), but only with high rate of coverage. It can also increase these problems that the common milkweed can be serve as reservoir and host for viruses, other pathogens and pests.Because of the importance of common milkweed and in spite of demand to develop effective biological control, until now has not been developed a proper control program against A. syriaca. The aim of our research was to identify the necrotrophic fungal pathogens, which were involved in notable disease occurrence on this weed in different parts of Hajdúság region of Eastern-Hungary in 2016.To the isolation of fungi from leaves and their identification were based on morphological colony characters on potato dextrose agar (PDA) and Sabouraud dextrose agar (SDA). To the description of conidia features were used PDA for Alternaria and synthetic low-nutrient agar (SNA) for Fusarium species, respectively. The examination of axenic cultures revealed that the fungi isolated from the leaves of common milkweed were Fusarium sporotrichioides and Alternaria alternata.